From the Human Spine to Hyperredundant Robots: The ERMIS Mechanism. (8th September 2013) - Georgilas, Ioannis; Tourassis, Vassilios
Abstract : Mechatronics are occasionally inspired by nature for joint designs in order to exploit the advantages of the biological ones in terms of mobility and articulation. Within this context and based upon the human spine for structure and actuation, the authors will present a novel hyperredundant mechanism, named ERMIS. The muscle-skeletal system of the human trunk will be described and modelled, and the elements that are being replicated by the mechanical analog will be analysed. It will be shown that the vertebrae-intervertebral disk arrangement can be emulated by a spherical-type configuration, the proposed Disk-Ball-Disk joint. Furthermore, the muscle actuation system is being recreated by a system of wires and pulleys. The relevant kinematic models will be developed, and both simulation and experimental data to evaluate its operation will be demonstrated.